Dimensões relevantes do planeamento estratégico territorial (PET) na promoção de turismo sustentável - Silva, Adriana Isabel Teixeira da (2014)
Strategic territorial planning (STP) is a basic and essential activity to primarily ensure quality, sustainability and competitiveness of tourist destinations. This article is based on the analysis of relevant STP dimensions in promoting sustainable tourism. Therefore, models of sustainable planning will be analyzed according to the development of tourist destinations, sustainable coastal current cases, and the territorial planning strategies used by these cases. Afterwards, typical destination’s structural instabilities will be analyzed considering inadequate planning and development techniques. It is hoped that the conclusions will contribute in some way for a more effective sustainable tourism planning.